2018
DOI: 10.3390/w11010022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Texture on Water Movement of Porous Ceramic Emitters: A Simulation Study

Abstract: Choosing reasonable design parameters for ceramic emitters used in subsurface irrigation is important for reducing the deep percolation of water and improving the water use efficiency. Laboratory experiments and numerical simulations with the HYDRUS-2D software were carried out to analyze the effect of soil texture on the infiltration characteristics of porous ceramic emitters used for subsurface irrigation. HYDRUS-2D predictions of emitter discharge in soil and wetting front are in agreement with experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The results of a study using porous ceramic emitters buried in two types of soil (Cai et al 2018) were similar to those found in this study: the flow rate of the emitter dropped rapidly at the beginning of the test and then gradually decreased until it reached a stable value.…”
Section: Resultssupporting
confidence: 85%
“…The results of a study using porous ceramic emitters buried in two types of soil (Cai et al 2018) were similar to those found in this study: the flow rate of the emitter dropped rapidly at the beginning of the test and then gradually decreased until it reached a stable value.…”
Section: Resultssupporting
confidence: 85%
“…They concluded that the recommended design parameters depended upon soil type, climate condition, irrigation intensity, and plant type. Another paper conducted by Cai et al (2019a) was to test a ceramic patch in a subsurface irrigation line to control the saturated zone in soil profile created by the Pertanika J. Sci. & Technol.…”
Section: Review Of Literature Of 2015-2019mentioning
confidence: 99%
“…The irrigation with porous ceramic emitters works best in clayey soils, while in sandy soils with a low water holding capacity, deep percolation may be produced. Cai et al (2019) even suggest the addition of a water retention agent to prevent deep percolation. This appears rather unrealistic to be used in the context of European agricultural practice.…”
Section: Introductionmentioning
confidence: 99%